Perancangan Ontologi Semantik Representasi Digital Oleh - Oleh Khas Bali - Ngakan Made Alit Wiradhanta,; Ida Bagus Made Mahendra, (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2023)
Bali Island, also known as the Island of the Gods, is a popular tourist destination for those who want to enjoy its breathtaking natural beauty. However, many tourists face difficulties in finding authentic Balinese souvenirs to bring back home. To address this issue, a system is needed to assist tourists in easily and quickly finding information about unique Balinese souvenirs using ontology, a semantic web knowledge base. The semantic web is a website development approach aimed at automation and understanding the meaning and relationships of data, resulting in a web experience tailored to visitors' preferences. This research aims to develop an ontology model to be used in the domain of Balinese souvenirs. The ontology design is developed using the Protégé application, where the ontology model is structured with hierarchical classes, slots, properties, and other elements. It is expected that this ontology model will provide information related to semantic web-based application metadata pertaining to Balinese souvenirs.
Keywords: Ontologi, Oleh - Oleh Khas Bali, Web Semantik